DAMPAK KEBIJAKAN PERATURAN DAERAH NOMOR 4 TAHUN 2011 TERHADAP PAJAK RESTORAN DAN TINGKAT REALISASI PAJAK RESTORAN DARI TAHUN 2007 SAMPAI 2012 - DYAN PRAVITASARI, FEMKA Dyan (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this research is to know the changes that occurred after the new regulation was issued and to find out the level of realization of the reception and the restaurant tax growth.The method used is a qualitative descriptive. The results of this research can be known to be a tax receipt system using just my assesment, bakery and catering in the tax area, limit the imposition of minimum tax imposed in the omzet new rule 15 milion and growing acceptance of the tax sector in increasing althought realization does not match the expected targets.Keyword: restaurant tax, region tax, growing realization